A PRESENÇA PÚBLICA DA IGREJA NA CIDADE: Análise das práticas pastorais da Igreja Metodista em Belo Horizonte (1982 a 2006) frente aos desafios das transformações socioculturais - Barreto, Jonas Mendes (2013)
The research developed deals with this crisis of meaning in a society in transformation process, with the main purpose of pointing the challenges and possibilities of redefinition of the Methodist praxis in the urban context. This transformation process is characterized by various elements that constitute the formation of this new religious cultural scene, as the urban question, the hybridization of religious practices, spirituality without religion, privatization of faith, religious pluralism, secularization, religious transit, the emergence of new religious proposals, the loss of autonomy of various traditional institutional mediations. The hypothesis is that the phenomena that characterize this present time of change have affected the Protestant mission churches, including the Methodist Church. The investigation of these phenomena, based in theoretical foundations, aims to analyze the impact of changes in socio-cultural context of the Methodist Church and some of its consequences in the religious field, especially in the urban reality of the Methodist Church in Belo Horizonte, in the period from 1982 to 2006. The characteristic culture of this time of change demanded new paradigms of Methodism pastoral action to the urban context in Belo Horizonte, however the Methodist Church was not able to contemplate in documents Plan For Life and Mission (1982) and Gifts and Ministries (1987) an effective response to the challenges of this time of transformation. Amid the changes that have occurred in society, the Methodist Church has tried new forms of organization structure and changes in its documents Four-year Plans, Five-Year Plans, Plan for Life and Mission of the Church and Gifts and Ministries. But the pastoral actions of Methodism in Belo Horizonte did not result in pastoral praxis that would respond to changes in society. The Methodist Church in Belo Horizonte was not able to perceive these changes and hence the need to change the traditional pastoral functions, facing the new sociocultural challenges. The specific objective of this research is therefore to understand how this new cultural paradigm, in view of the public presence, has affected the Methodist Church in Belo Horizonte and how it has responded to the challenges of its pastoral practices of evangelism, social action and education. For sounding responses that will meet these challenges, the pastoral practices of the Methodist Church in Belo Horizonte, the sociocultural transformations and how they affected the pastoral mode of Methodism, will be analyzed, forcing it to reinterpret itself and taking a critical and transformative stand in the society to reframe the Methodist praxis in the urban context. .